Main systems of faults of Windy Belt: succession and conditions of formation - S. V. Mezhelovskaya; A. K. Korsakov; A. D. Mezhelovskiy; A. K. Narvas (Известия высших учебных заведений: Геология и разведка)
Geological-structural investigations on the all area of Windy Belt allowed distinguishing three systems of gentle dipping zones of faults: Kirichinskaya, Tokshinskaya, Bulatovskaya systems and the system of steep faults of different directions of dipping. Gently dipping zones correspond to the stages of compression of Windy Belt with its interaction with boundary structures (Belomorsky Belt and Karelian granite - greenstone region). The system of steep dipping faults formed in the tension environment.